Bacterial biota of women with bacterial vaginosis treated with lactoferrin: an open prospective randomized trial. (1st January 2017) - Pino, Alessandra; Giunta, Giuliana; Randazzo, Cinzia L.; Caruso, Salvatore; Caggia, Cinzia; Cianci, Antonio
ABSTRACT: Background: Bacterial vaginosis is the most frequent condition associated to the vaginal microbiota imbalance, affecting about the 40–50% of women in the world. Even if antibiotics are effcetive for bacterial vaginosis treatment a long-term recurrence rates, higher than 70%, is recorded. Lactoferrin is an iron-binding glycoprotein with bacteriostatic and bactericidal properties. It owns the ability to protect the host against infection, by binding and regulating the iron needed for the bacterial proliferation. Objective : The present study was an open prospective randomized trial (registration no. SHI-EVE-2014.01) aimed at characterizing the bacterial biota of women affected by bacterial vaginosis (BV) and assessing the effects of two different lactoferrin concentrations (100 mg and 200 mg vaginal pessaries) on the composition and dynamics of the vaginal bacterial biota. Design : Sixty women with BV were recruited and randomized into two groups to receive lactoferrin pessaries for 10 days. Clinical evaluation was based on Amsel criteria and Nugent scores. Culture-dependent methods and Ion Torrent PGM sequencing of the 16S rRNA gene were applied to study in depth the overall structure of the vaginal bacterial biota and its dynamics during the treatment. Results : Vaginal lactoferrin administration modified the vaginal microbiota composition in patients with BV. During treatment, both 100 mg and 200 mg lactoferrin vaginal pessaries significantly decreased the occurrence of bacteria associated with BV, such as Gardnerella, Prevotella, and Lachnospira, and increased the occurrence of Lactobacillus species. The bacterial biota balance was maintained up to 2 weeks after treatment only in women treated with 200 mg lactoferrin pessaries. Conclusions : This study indicates that lactoferrin could be proposed as an alternative therapeutic approach for BV. Our data showed, for the first time, the dominance of Lactobacillus helveticus species during and after vaginal lactoferrin treatment.